A comparison study examining the impacts of carbon forestry integration within New Zealand sheep and beef farms upon economic and environmental performance : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agribusiness at Massey University, New Zealand - Walker, Cameron (Massey University, 2021)
In the face of a changing climate, New Zealand has committed to reducing its greenhouse gas emissions. Emissions from New Zealand pastoral agriculture form a large proportion of the nation’s total greenhouse gas emissions, and therefore, significant reductions must be made by this sector. Carbon forestry has been identified by multiple groups as a means of achieving these reductions from pastoral farmland. However, without adequate information regarding the economic and environmental impacts of integrating carbon forestry into sheep and beef farms, it is likely that adoption rates by farmers will be low. Therefore, this study is a comparison study that evaluates two sheep and beef case study farms within the Hawke’s Bay Region to compare and contrast the impacts of integrating carbon forestry onto marginal pastoral land. Several modelling software systems were used to model base scenarios for each farm, with mitigation scenarios incorporating carbon forestry then modelled to report changes in economic and environmental performance of the case study farms. It was found that the economic and environmental impacts of carbon forestry integration are dependent upon the relative performance of the pastoral farming enterprise and type of carbon forestry undertaken on marginal pastoral land. Factors such as physical productivity, pastoral management practices, forestry management practices, and size of area of afforestation were some of the determining factors. Whilst the environmental impacts of carbon forestry integration do vary depending on several factors, and between farms, it can be concluded from this research that integration of carbon forestry will reduce gross greenhouse gas emissions (9.0% to 66.1%) and net greenhouse gas emissions (51.4% to 322.5%), as well as nitrogen root zone loss (9.4% to 56.0%) and phosphorus root zone loss (8.6% to 51.7%), from sheep and beef farms when integrated upon marginal pastoral land. However, the economic impacts of carbon forestry are far more subject to farm heterogeneity, and therefore, to understand the impacts of carbon forestry integration upon economic performance an in-depth analysis of the property needs to be undertaken.
Keywords: 300208 Farm management, rural management and agribusiness